A simplified coupled model for predicting dynamic processes of vehicle impact on pier columns. (July 2022) - Wang, W.; Chen, J.; Zhou, R.X.; Zhong, J.
Abstract: Vehicle collision upon pier columns has become a very severe threat to the structural safety and normal operation of highway bridges. Substantial scientific investigations were therefore conducted over the past several decades to understand the mechanical phenomenon involved in vehicle-pier collision events through experimental and finite-element (FE) numerical approaches. Whilst both approaches require a substantial investment of time and effort, the equivalent static approach that is easy for computation has been adopted by many design specifications. However, the static method ignores important dynamic effects such as inertia effects, which may lead to inaccurate prediction results. Therefore, the development of numerically accurate and computationally efficient simplified impact models using macro-level elements to replicate the complex FE models of vehicles and impacted structures has drawn the attention of many researchers. In this paper, a simplified mass-spring model using three non-linear springs working in parallel is proposed to replicate a realistic truck model, and a set of regression formulas are developed to calculate the spring parameters which are correlated to pre-specified design parameters including truck weight, impact velocity, and cross-section dimension of a pier column. By coupling the mass-spring model to a pier column which is discretized into a series of lumped masses and fiber beam elements, a coupled model is developed to predict the time-histories of impact forces and dynamic structural responses during impact. Benchmark numerical data generated by detailed FE simulations are employed to calibrate the proposed coupled model, which is shown to be able to provide very reliable predictions of the dynamic processes for different impact scenarios.